Analysis of playing time of elite male water polo players at the 2011 World Championships - Enomoto, I.; Suga, M.; Omoto, Y.; Hara, A. (World Congress of Performance Analysis of Sport IX, 2012)
At the FINA Water Polo World Championships, the preliminary round of a match lasts 3 days, followed by the final round held over 4 days. Men`s and women`s matches are held on alternate days. Changing the player is permitted anytime during the official match of 32 minutes. The physical fitness of each player, and the tactical ability of the team determine the playing time for each player. Therefore, the analysis of playing time of opponents may help in planning scouting tactics. The official match scoresheet, including the playing time of each player, of the international water polo tournament can be acquired from the official web site. The purpose of the current study is to analyze the significance of the playing time of elite male water polo players in the World Championships 2011, by conducting a statistical analysis of the official scoresheet. The official score sheets of 48 men`s water polo matches held at FINA World Championships 2011 (Shanghai, China) were obtained from the web site: http://www.omegatiming.com/index_home.htm#waterpolo/racearchives/2011/WP_Shanghai/res.html. The playing time of 177 male field players from 16 countries were selected. The average (SD) age and participation rate were 26.7(4.3) years and 6.0(0.7) matches, respectively. Each player participated in 5 to 7 matches during tournament. The average playing time, the coefficient variance (CV) of playing time for each player, and Pearson`s correlation coefficient between the average playing time and CV for each player were computed. PASW Statistics 18.0 was used for the statistical analysis. Average (SD) playing time of every player was 17.5(3.8) minutes per match. Average (SD) CV of every player was 0.27(0.24). The correlation coefficient between the average playing time and CV for every player was -0.64 (p < 0.01). Average (SD) age and playing time of centerback (CB; n = 43), driver (DR; n = 99), and centerforward (CF; n = 35) were respectively 27.5(4.4) years and 17.8(5.6) minutes, 26.0(4.1) years and 17.6(6.6) minutes, and 27.5(4.8) years and 16.8(4.6) minutes. Average (SD) CV of CB, DR, and CF were 0.25(0.15), 0.30(0.29), and 0.19(0.11), respectively. The correlation coefficient between the average playing time and CV for CB, DR, and CF were -0.73, -0.69, and -0.44, respectively (p < 0.01). The playing time for the leading 4 countries in this tournament were analyzed. Average (SD) age and playing time of ITALIA (ITA, 1st place, n = 11), SERBIA (SRB, 2nd place, n = 11), CROATIA (CRO, 3rd place, n = 12), and HUNGARY (HUN, 4th place, n = 11) were respectively 28.4(3.6) years and 18.0(4.7) minutes, 25.7(2.7) years and 18.5(7.3) minutes, 27.2(4.8) years and 16.0(3.8) minutes, and 29.7(3.7) years and 18.0(8.0) minutes. Every country participated in 6 matches during this tournament. The number of field players from CRO was higher than that from other countries. This might be the reason that the average playing time of CRO was lower than that of other countries. Average (SD; country code) CV of the playing time for each player was as follows: 0.22 (0.12; ITA), 0.29 (0.16; SER), 0.32 (0.18; CRO), and 0.26 (0.29; HUN). The correlation coefficient between the average playing time and CV for ITA, SRB, CRO, and HUN was -0.66 (p = 0.029), -0.70 (p = 0.017), -0.38 (p = 0.22), and -0.69 (p = 0.018), respectively.